2009
DOI: 10.3109/09638280903374121
|View full text |Cite
|
Sign up to set email alerts
|

Needs, barriers and facilitators experienced by spouses of people with aphasia

Abstract: Results confirm the long-term needs of spouses in adjusting to the aphasia of their partner, as well as the limited services available to them. Many of the needs reflected spouses' concerns about their partner, while others were a consequence of their caregiving role as well as the unavailability of support. Spouses of people with aphasia should have access to support during and after rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 46 publications
3
65
0
1
Order By: Relevance
“…The median age of participants was 78. This study sample showed a spread of deprivation (deciles ranged [3][4][5][6][7][8][9] but was skewed toward people from the least deprived areas (median decile 7.5). Initial questioning about problems revealed that the meaning of a 'problem' varied between individuals and issues, and some rejected the word 'problem', therefore, these have been termed 'issues'.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of participants was 78. This study sample showed a spread of deprivation (deciles ranged [3][4][5][6][7][8][9] but was skewed toward people from the least deprived areas (median decile 7.5). Initial questioning about problems revealed that the meaning of a 'problem' varied between individuals and issues, and some rejected the word 'problem', therefore, these have been termed 'issues'.…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of unmet needs are reported by stroke survivors in the longer term, including those which persist from six months to fifteen years [4][5][6][7]. Mapping to frameworks such as the Disability Creation Process [5], and the International Classification of Functioning, Disability and Health [7] demonstrates that stroke survivor needs can relate to a range of factors.…”
Section: Introductionmentioning
confidence: 99%
“…The number of 41 inclusions from 263 eligible clients (16%) was lower than expected, based on perceived needs previously outlined by partners [47] [48]. This may be due to several factors including attitudinal factors from both service providers and service users as well as 25 organisational factors such as SLT staffing.…”
mentioning
confidence: 75%
“…The older family members wanted to keep external framework of the family in good condition and they were extremely happy to the care of the stoke patient. This helped them to cope during the difficult times [36,44,45] . The very exact information distributed in a website (StrokEngine, Caretalk, Caring -Web) developed in Canada and the USA which dealt with stroke and rehabilitation, and the possibility to be in contact with the healthcare professionals and peers, received positive feedback from family members.…”
Section: Rebuilding Of Lifementioning
confidence: 99%
“…Recognizing the needs of the family members from the first moments are important [36][37][38] . The family members whose sick relative was in the hospital longer had a better opportunity to plan for the patient's discharge with the healthcare staff.…”
Section: Rebuilding Of Lifementioning
confidence: 99%